Enhancement program for inclusive kindergarten in Southern Philippines - Princesa Zerrudo, Adora (TẠP CHÍ KHOA HỌC TRƯỜNG ĐẠI HỌC TÂN TRÀO, 2021)
This study focused on the evaluation of how inclusive kindergarten schools implemented the inclusion of kindergarten with disabilities. It determined the level of implementation of inclusive education practices; the extent of attainment of the program; recognized best practices and challenges met by the respondents. This research employed the descriptive evaluative design and qualitative method through a focus group discussion with the principals and teachers. Results showed that the implementation of inclusive kindergarten program is generally observed to be very high; attainment of the program objectives/outcomes yielded a high level of implementation with approximately 61%-80% target indicators; best practices include dedication of teachers, appropriate school environment, in-service trainings conducted, curriculum modification and support of parents, while challenges met consisted of attitude of teachers towards inclusive education, workload of teachers, acceptance of parents, assessment and strategies in handling children with behavioral problem. Hence, the study concluded that inclusive education in Davao Region is highly implemented. It is recommended that intensive trainings and seminars on special education-related topics for both regular and SPED teachers be designed; intensify support to kindergarten teachers in terms of professional and financial needs; and child find should be conducted both by SPED teachers and regular teachers.